The Demographic Background of Employees’ Wages of Aceh in 2017 (Case Study in Ex-Conflict Areas) - Marini, Yushita (International Journal of Psychosocial Rehabilitation, 2020)
Some area in Aceh are former military operation conflict that have occurred in Indonesia, After the conflict abated, there wa a significant gap in the wage receipts of employees’ in Aceh. This research analyzed the factors that influence the wage earning of employees and the effect of factor on the wage in Aceh in 2017, particularly in the demographic background of former conflict areas in Aceh. This research used primary data from the 2017 National Labor Force Survey (Sakernas) conducted by the Central Statistics Agency (BPS). The object of research were employees who receive wages/salaries and benefits, the form of money and goods. The variables used in addition to wages are namely the level of education, age, sex, years of work, and demographics of the work area (urban/rural, ex-conflict/non-conflict). The purpose of this research was to determine the factors that influence wage levels and determine the effect of factor on wage levels in Aceh using Multiple Classification Analysis (MCA), inferential statistical techniques, logistic regression methods and the IBM SPSS program. Variables that had a significant influence with wages base on: the level of diploma education obtains wages 51,72% higher than high school, 19,75% wages of men are higher than women, for wages at productive age (20- 60 ) 25,99% higher. Wages in urban areas were 66,14% higher than in rural areas, but for ex-conflict areas there was a decrease in wages of about 74,03% of the factors that influence the variable wage acceptance of employees.